Fusion of raft-like lipid bilayers operated by a membranotropic domain of the HSV-type I glycoprotein gH occurs through a cholesterol-dependent mechanism1. Issue 15 (21st April 2015) - Vitiello, Giuseppe; Falanga, Annarita; Petruk, Ariel Alcides; Merlino, Antonello; Fragneto, Giovanna; Paduano, Luigi; Galdiero, Stefania; D'Errico, Gerardino
<x xml:space="preserve">Abstract</x> Specific interactions between cholesterol and the gH625 peptide are able to drive lipid re-arrangement resulting in lipid raft fusion.